PURE BORROWING TECHNIQUE IN INDONESIAN TRANSLATION OF NOVEL ENTITLED LITTLE WOMAN BY LOUISA MAY ALCOTT - Badriyah Ulfah (Journal of English Educational Study (JEES), 2022)
Pure borrowing technique is translation technique that corresponds to Stylistique Comparee du Francais et de L’Anglais (SCFA) by Vinay in 1977. By using the technique, this research was intended to analyze the pure borrowing words and the part of speech that can be found in the Indonesian translation of Little Woman novel by Louisa May Alcott.  The qualitative descriptive approach was used to achieve the objective of the study. The data was collected by reading both the Indonesian and English versions of the novel. The result shows that 119 pure borrowing words were found from all 23 chapters of the book with 628 total frequencies. The parts of speech found are noun, adjective, verb, and interjection with an additional 2 clauses and 1 phrase.  It was also found that most of the pure borrowing words in the novel have the translation in the target language, but the translator chose to use the pure borrowing technique. However, despite several pure borrowing words, the Indonesian version of Little Woman Novel can be still well-received by Indonesian native language readers.